Rainfall‐induced landslide inventories for Lower Mekong based on Planet imagery and a semi‐automatic mapping method. (9th January 2022) - Amatya, Pukar; Kirschbaum, Dalia; Stanley, Thomas
Abstract: Fatal landslides occur every year during the rainy season (June–November) in the Lower Mekong Region (LMR). There is an urgent need to develop a landslide early warning system in the LMR. In collaboration with the Asian Disasters Preparedness Center and NASA's SERVIR Programme, we are regionalizing the global Landslide Hazard Assessment System for Situational Awareness model for the LMR (LHASA‐Mekong). A robust set of landslide inventories are needed to effectively train the machine learning‐based LHASA‐Mekong model. In this study, the Semi‐Automatic Landslide Detection (SALaD) system was modified by incorporating a change detection module (SALaD‐CD) to produce rainfall event‐based landslide inventories using pre‐ and post‐imagery from RapidEye and PlanetScope for various locations in the LMR that were identified based on media and government reports. These rainfall‐induced landslides are published as initiation points for ease of use. In total, we created 22 inventories: 2 in Laos, 4 in Myanmar, 1 in Thailand and 15 in Vietnam. These inventories are being used to train the LHASA‐Mekong model and quantify the effects of Land use/Land cover change on landslide susceptibility. These open data will be a valuable resource for advancing landslide studies in this region. Abstract : Twenty‐two landslide mapping locations identified from media and government reports in the Lower Mekong Region.